DETERMINAN ANGKA KUMAN PADA MINUMAN AIR TEBU PEDAGANG KAKI LIMA KECAMATAN PONTIANAK TENGGARA - Dhea Vanezza; Selviana; Dedi Alamsyah; Helfi Nolia (Poltekkes Kemenkes Medan, 2024)
Foundation: Sugarcane juice is one of the handled sugarcane drinks that is very famous with general society. The goal of this study was to find out what factors influence the number of germs in sugarcane juice drinks sold by street vendors in the Pontianak Tenggara District. Cross-sectional analysis was used in this study. The examination test was 30 Sugarcane Juice. The Spearman rank correlation test was the one that was utilized. Results: The relationship between Personal Hygiene and Filter Cleanliness (p value = 0.001) is significant (p = 0.001). In addition, there is no correlation between the number of germs in sugarcane juice drinks in Pontianak Tenggara District and Storage Place (p value = 0.061). In conclusion, sugarcane juice traders in Pontianak Tenggara need to keep the filter clean to prevent contamination from vectors and dust on the streets and to keep traders' personal hygiene.